Simultaneous and Consecutive Drainage of Bilateral Chronic Subdural Hematoma: A Randomized Controlled Trial - Omer AKAR; Hasan Kamil SUCU; Selin BOZDAG (Neurologia Medico-Chirurgica)
Chronic subdural hematoma (CSDH) is one of the most common types of intracranial hemorrhage, particularly in elderly individuals. Although most patients present with unilateral CSDH, bilateral involvement is not rare. Furthermore, bilateral CSDHs are associated with rapid deterioration and poorer outcomes because of a higher risk of brain herniation than unilateral hematomas. The most contentious issue is the potential herniation of the medial temporal lobe, which remains on the unevacuated side during the brief interval between right and left procedures. We compared simultaneous burr-hole craniostomy with consecutive burr-hole craniostomy for treating bilateral CSDH and to determine whether consecutive evacuation is riskier in terms of brain stem complications. Over a 6.5-year period, patients with bilateral CSDH who had an indication for operation were allocated into two groups randomly. The first group (n = 18) underwent simultaneous evacuation, and the second group (n = 25) underwent consecutive evacuation. Glasgow Coma Scale and Markwalder grades were recorded during the postoperative period. Patients were followed up during the inpatient period and postoperatively at 1, 3, 6, and 12 months after discharge. Mortality, morbidity, surgical complications, reoperation, and, as a combination of all of these, treatment success rates were compared. Treatment success rates were worse in patients with mixed-density hematomas and in female patients at the end of 12 months, but there was no significant difference between the simultaneous and consecutive evacuation groups at any time. Therefore, the choice of technique can be decided by the surgeon.